Combination of external and internal fixation in the treatment of an exposed fracture of the tibial pylon. Case Presentation - Yaniel Truffin Rodriguez; Osmany Pérez Martínez; Sergio Miguel Samón Matos; Annia Lázara López Hernández (Medisur)
Exposed fractures of the tibial pylon are infrequent lesions that are associated with the appearance of multiple complications derived from the intensity of the traumain addition to the real sepsis possibility of soft tissues or bone and bone consolidation disorders related to the affected zone. Adequate management of these conditions by the medical staff avoids the appearance of important complications, for this reason it was decided to share the experience in the management of these conditions by presenting a case.